Implementasi Ham Pada Siswa Kelas VIII SMPN 1 Kayen Kidul - Widodo Pujo Laksono; Salfa Amanda Putri; Epirin Kusuma; Irawan Hadi Wiranata (Philosophiamundi, 2024)
Implementation of Human Rights is the application of ways for humans to respect each other; this is because humans cannot live alone; humans need other people to fulfil all their needs. The implementation of human rights in the world of education is very important. By implementing human rights from an early age, it is hoped that the nation's future generations will be able to implement human rights in the future. The aim of this research is to find out how human rights are implemented at SMPN 1 Kayen Kidul School. The method used in this research is descriptive qualitative with a literature approach. Based on the results of research, the implementation of human rights at SMPN 1 Kayen Kidul Masi is still very lacking, with several cases encountered, such as harassment of skin colour and harassment of parents' names. The conclusion of this research is that it is necessary to introduce material about.